2017
DOI: 10.1080/10641955.2017.1291673
|View full text |Cite
|
Sign up to set email alerts
|

Increased placental sFlt-1 but unchanged PlGF expression in late-onset preeclampsia

Abstract: High sFlt-1 concentrations may account for diminished maternal serum PlGF levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Finally, we did not evaluate the release of this protein from the placenta into the maternal circulation for future use of predictive estimates with simple blood tests. Huppertz et al [ 45 ] have demonstrated the importance of obtaining results of a placental protein from diversified origins (placenta, serum, amniotic fluid) to reach a comprehensive understanding of the actual origin of the measured protein and further verify its role in the placental pathology in PE [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not evaluate the release of this protein from the placenta into the maternal circulation for future use of predictive estimates with simple blood tests. Huppertz et al [ 45 ] have demonstrated the importance of obtaining results of a placental protein from diversified origins (placenta, serum, amniotic fluid) to reach a comprehensive understanding of the actual origin of the measured protein and further verify its role in the placental pathology in PE [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Total mRNA was Women were divided into four subgroups: early-onset PE (n = 7), lateonset PE (n = 18), FGR (n = 13), and a control group (n = 16).…”
Section: B7-h4 Mrna Expression In Placental Villous Tissue -Study Pmentioning
confidence: 99%
“…The explanation could be related to PLGF decrease with labor duration;48 PLGF (both mRNA and protein) has also been observed as decreasing in labor samples 48. Most such studies have been carried out in maternal serum 25,49,50…”
Section: Discussionmentioning
confidence: 99%